2010
DOI: 10.1021/ja1036429
|View full text |Cite
|
Sign up to set email alerts
|

Modifying the Size and Shape of Monodisperse Bifunctional Alkaline-Earth Fluoride Nanocrystals through Lanthanide Doping

Abstract: In this communication, a simple route for modifying the uneven size and shape of alkaline-earth fluoride nanophases to monodisperse ultrasmall nanospheres through lanthanide doping is offered. These nanospheres are found to exhibit bifunctionality, i.e., tunable upconversion emissions as well as proper paramagnetism, making them potentially applicable in the biological field. The synthesis strategy, which involves doping of an impurity with a different valence than the cation in the nanophase, might be useful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
192
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 292 publications
(200 citation statements)
references
References 36 publications
6
192
0
2
Order By: Relevance
“…Furthermore, since the light-grown NPs evaporate with a characteristic time which depends on their shape, the time spent by an atom in a cluster before resuming its random walk along the pore is in turn affected by the light. Therefore, light drives the overall atomic diffusion-reaction dynamics inside the porous matrix.Unlike the conventional NPs production techniques, relying mainly on chemical [17] and photochemical approaches [9] or laser ablation in liquids [18,19], the method presented here is based on the reversible light-induced modifications of the atomic adsorption/desorption and cluster nucleation rates. This approach allows for the observation and control of the dynamics of the NPs' formation/evaporation processes.…”
mentioning
confidence: 99%
“…Furthermore, since the light-grown NPs evaporate with a characteristic time which depends on their shape, the time spent by an atom in a cluster before resuming its random walk along the pore is in turn affected by the light. Therefore, light drives the overall atomic diffusion-reaction dynamics inside the porous matrix.Unlike the conventional NPs production techniques, relying mainly on chemical [17] and photochemical approaches [9] or laser ablation in liquids [18,19], the method presented here is based on the reversible light-induced modifications of the atomic adsorption/desorption and cluster nucleation rates. This approach allows for the observation and control of the dynamics of the NPs' formation/evaporation processes.…”
mentioning
confidence: 99%
“…14 Wang et al 15 demonstrated that addition of Gd 3+ could control the size, phase, and upconversion emission of NaYF 4 . Similarly, Chen et al 16 reported that lanthanide doping of an alkaline-earth metal fluoride resulted in significantly improved monodispersity. A common strategy for enhancing the luminescence is to tune the doping concentration of lanthanide ions, 17,18 but high doping level may lead to concentration quenching, particularly in the short-wavelength spectral region, which may deteriorate the luminescence intensity.…”
Section: Introductionmentioning
confidence: 93%
“…Among the established approaches, thermal decomposition [43][44][45][46], high-temperature coprecipitation [47][48][49] and hydro (solvo) thermal methods [50][51][52] are the most popular synthetic routes. These methods commonly make use of the organic surfactants to control the nucleation and growth of the nanocrystals.…”
Section: Controlled Synthesismentioning
confidence: 99%